Fundamental electron-transfer and proton-coupled electron-transfer properties of Ru(iv)-oxo complexes. Issue 35 (22nd July 2019) - Kotani, Hiroaki; Shimomura, Hinatsu; Horimoto, Momoka; Ishizuka, Tomoya; Shiota, Yoshihito; Yoshizawa, Kazunari; Yanagisawa, Sachiko; Kawahara-Nakagawa, Yuka; Kubo, Minoru; Kojima, Takahiko
Abstract : Reorganization energies ( λ ) of electron transfer (ET) and proton-coupled ET (PCET) from electron donors to isolated Ru IV (O) complexes were determined to be in the range of 1.70–1.88 eV (ET) and 1.20–1.26 eV (PCET). Abstract : Isolation and characterisation of Ru IV (O) complexes were accomplished to investigate their fundamental electron transfer (ET) and proton-coupled ET (PCET) properties. Reorganisation energies ( λ ) in electron transfer (ET) and proton-coupled ET (PCET) from electron donors to the isolated Ru IV (O) complexes have been determined for the first time to be in the range of 1.70–1.88 eV (ET) and 1.20–1.26 eV (PCET). It was suggested that the reduction of the λ values of PCET in comparison with those of ET should be due to the smaller structural change in PCET than that in ET on the basis of DFT calculations on1 and 1e − -reduced1 in the absence and presence of TFA, respectively. In addition, the smaller λ values for the Ru IV (O) complexes than those reported for Fe IV (O) and Mn IV (O) complexes should be due to the lack of participation of dσ orbitals in the ET and PCET reactions. This is the first example to evaluate fundamental ET and PCET properties of Ru IV (O) complexes leading to further understanding of their reactivity in oxidation reactions.